Die Schrecken des Eises und der Finsternis von Christoph Ransmayr, eine chronotopische Grenzüberschreitung, von Innen- und Außenräumen, Dekonstruktion von Schreckensgeschichten - Rafika Beghoul (Edile (Edition et diffusion de l'écrit scientifique), 2024)
We read Christoph Ransmayr’s novel « Die Schrecken des Eises und der Finsternis » as a « setting » (p. 21), a « play », but also as « scenery », which is representative of a polyphony, intermediality, historical complexity, factuality and transhistoricity. His transhistorical construct, which presents two explorations (1872 and 1981) in a polyphonic score of voices, quotations from journals, chronicles and multiperspectivity, is introduced by a « we ». His narrative technique stages a double, an author-figure, in Mazzini (1981), the writer and « inventor » of realities, who measures the latter according to his imagination. Conversely, the novel questions the principle of probability and mimesis as ideologem. In both explorations, Ransmayr reconstructs the other unwritten history of an inner, invisible world, the counter-history of the weak, injured sailors, also that of fear and horror. Spaces, topographies, but also the objectification and instrumentalisation of bodies are at the heart of his poetics and criticism. Ransmayr exchanges the representativeness of truth systems, presents the forgotten names through official archives as exclusion, truth and justice to be fulfilled, as well as cracks, gaps and voids to be filled in a historiography whose cartography overlaps with an earth history. Its anachronism serves to rehabilitate the other truth of the weaker, the bowed bodies of sailors, about their fears, loneliness and abandonment in the infinite darkness of an Arctic winter. Weyprecht and Payer rise to become critical, border-crossing voices emancipated from discourses of power. Enigmatic tropical landscapes and allegories are also transformed into a denunciation of colonial plans and cartography of empty spaces to be filled in. The polyphonic novel and its aesthetic transgressions foreground the ideologisation of theories, the incomplete historiography, and archaeology of violence as well as the circularity of history as programmatic problems.